International Symposium on Wellness & Healthy Lifestyle Yogyakarta, Indonesia 25 Februari 2010 - Wan Rosli, Wan Ishak (Pusat Pengajian Sains Perubatan, 2010)
The interest in food rich in antioxidants and dietary fibres, has grown in the current decade and the significance of these food constituents has led to the development of a large market for antioxidant and fibre rich products and ingredient. The intake of dietary fibre and phytochemicals have been linked to the maintenance of health and protection from diseases such as colon cancer, cardiovascular diseases, hyperglycemia, gastrointestinal unrests and many other degenerative diseases. Another plausible reason for the addition of dietary fibers in some formulations can be the improvement of the nutritional properties, sensory quality and reduction in the production costs of the food products. This paper discusses the development of dietary fibre from cornsilk as a health food ingredient. Cornsilk or Zea mays hairs are normally discarded during the preparation of young corn cob as vegetable despite the richness in dietary fibre, antioxidant and other important nutrients. The present study noted that dried cornsilk contained 38.4 g/1 OOg of total dietary fibre and 40.6 mg/1 OOg of total sugars, respectively. The addition of cornsilk powder in beef patties resulted in an increase in the nutritional compositions, water and fat holding capacity while maintaining the sensory quality of beef thus acceptable to consumers. Dried Zea mays hairs can therefore be used as alternative sources of dietary fibre in processed food and functional drink.